Demonstrating the lack of funds to pay court costs by a legal person within the meaning of article 103 of the law on court fees - Oślizło-Doskocz, Natalia (Studia Iuridica Toruniensia, 2019)
The provisions of Article 103 of the law on court fees relating to the exemption of legal persons from court costs are laconic. It is case law that specifies the obligations that are imposed on a party that wishes to obtain exemption from costs. This publication presents the scope of these obligations and procedural effects that arise for the party in the event of a failure to comply with them